Discrete π‐Stacks from Self‐Assembled Perylenediimide Analogues. Issue 43 (12th September 2019) - Su, Feng; Chen, Guangmei; Korevaar, Peter A.; Pan, Fangfang; Liu, Huijiao; Guo, Zongxia; Schenning, Albertus P. H. J.; Zhang, Hui‐Jun; Lin, Jianbin; Jiang, Yun‐Bao
Abstract: The formation of well‐defined finite‐sized aggregates represents an attractive goal in supramolecular chemistry. In particular, construction of discrete π‐stacked dye assemblies remains a challenge. Reported here is the design and synthesis of a novel type of discrete π‐stacked aggregate from two comparable perylenediimide (PDI) dyads (PEP and PBP ). The criss‐cross PEP ‐PBP dimers in solution and (PBP ‐PEP )‐(PEP ‐PBP ) tetramers in the solid state are well elucidated using single‐crystal X‐ray diffraction, dynamic light scattering, and diffusion‐ordered NMR spectroscopy. Extensive π–π stacking between the PDI units of PEP and PBP as well as repulsive interactions of swallow‐tailed alkyl substituents are responsible for the selective formation of discrete dimer and tetramer stacks. Our results reveal a new approach to preparing discrete π stacks that are appealing for making assemblies with well‐defined optoelectronic properties. Abstract : Look‐alikes : Reported here is the design and synthesis of a discrete π‐stacked aggregate from two comparable perylenediimide (PDI) dyads (PEP and PBP ). The criss‐cross PEP ‐PBP dimers in solution and (PBP ‐PEP )‐(PEP ‐PBP ) tetramers in the solid state are elucidated using single‐crystal X‐ray diffraction, dynamic light scattering, and diffusion‐ordered NMR spectroscopy. The chromophore look‐alikes uniformly embrace each other through π–π interactions and therefore form stable, discrete π‐stacks.